Improvement of Conservative Treatment of Periodontal Diseases Using Advanced Technologies - Xojimurodov Burxon Ravshanovich (Academia One Publishing, 2023)
Currently, the treatment of periodontal disease is a pressing issue due to its high frequency [1]. Patients with the first signs of periodontal disease (gingival inflammation, pain, and bleeding) remain poorly motivated and receive inadequate attention. Gingival inflammation begins in the gingival sulcus, where the quantitative and qualitative composition of the gingival fluid is altered. Polymorphonuclear leukocytes increase in the gingival sulcus, lysosomes are released from the cells under the influence of endotoxin, and degranulation occurs. Lysosome-derived enzymes (proteases, hydrolases, and lysozymes) interact with surrounding structures, causing and enhancing changes. Cellular mediators include histamine, serotonin, prostoglandins, lymphokines, and slow-reacting substances, the release of which is mediated by polymorphonuclear leukocytes, mast cells, and basophils. The biologically active components cause a rapid increase in vascular permeability, microcirculation is impaired, blood flow is slowed, thrombosis is increased, and vasculitis, hypocoagulation, hyperfibrinolysis, and secondary hypoxia develop. These changes cause depolymerization of the intercellular material of the gingival sulcus epithelium, creating vacuoles, fissures, and favorable conditions for deep penetration of toxins as well as bacteria into the underlying tissue. Microcirculatory disturbances increase vascular and tissue permeability. Disruption of defense mechanisms is accompanied by inhibition of regenerative processes, formation of pathological granulation tissue, and spread of inflammation to deeper tissues such as alveolar bone [1]. The complexity and multistep nature of the pathologic processes in periodontal disease creates the need for the use of drugs with diverse mechanisms of action, including anti-inflammatory drugs, analgesics, enzymes, drugs that stimulate microcirculation, drugs that improve immune defense, and many others that affect the etiologic links in the pathologic process. Although the pharmacotherapeutic armamentarium is vast, it should be noted that all drugs have side effects and toxicities associated with overdose, bioaccumulation, allergies and idiosyncrasies, and biological abnormalities. Many patients with periodontal disease have a constitutional condition and are treated by a medical doctor without considering an appointment with a dentist. More often than not, one pathology is replaced by another as a result of pharmacotherapy. In this regard, the development of treatments other than drug therapy and free from these drawbacks remains important
Keywords: treatment; periodontal; dentist; pathology